Hubungan Religiusitas dan Perilaku Prososial terhadap Kebermaknaan Hidup Karyawan yang di PHK Selama Pandemi Covid-19 - Damayanti, Rika; Aksir, Rahmad Purnama; Sikumbang, Prisilia Laurentika Taga; Bilqisti, Bela Sukma (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
The COVID-19 pandemic has caused employees and workers at the company to experience layoffs (layoffs) and difficulties in their lives. In interpreting his life, the individual must endure various challenges patiently and steadfastly, indicating a religious attitude. In addition to religiosity, prosocial behavior is also a factor in the meaning of life. This can be seen from the attitude of helping owned by the individual. The Covid-19 pandemic has had an impact on employees, especially psychologically. The emergence of psychological problems in individuals will impact the individual's prosocial behavior. Lack of religiosity when experiencing difficulties in life reduces the meaning of life for the individual, so individuals feel that their existence no longer has meaning and meaning. This study aimed to know the relationship between religiosity and prosocial behavior on the meaning of life in employees laid off during the COVID-19 pandemic. Quantitative methods carry out this research on each variable; a measuring instrument is a psychological scale with a Likert model. The data analysis technique used is a multiple regression analysis technique with the help of JASP 0.15.0 software. This study's results indicate a relationship between religiosity and prosocial behavior with the meaningful life of employees laid off during the COVID-19 pandemic.